Do cool shirts make a difference? The effects of upper body garments on health, fluid balance and performance during exercise in the heat - Engeroff, L.; Niederer, D.; Groneberg, D.; Vogt, L.; Engeroff, T. (BMC Sports Science, Medicine and Rehabilitation, 2023)
Objectives Due to climate change and major sport events in hot climate, temperature regulation during exercise is gaining relevance in professional and amateur sports. This study compares the effects of an upper body garment with water-soaked inlays, of a synthetic- and of a cotton shirt on health, fluid balance and performance during a high intensity exercise session in the heat.